2020
DOI: 10.5937/straman2003028d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employees' commitment on organizational performances

Abstract: This paper examines the impact of employees' commitment on the productivity of organizations in the Republic of Serbia. Employees' commitment represents the willingness of employees to make efforts for the benefit of the organization and the desire to remain in them. It can be seen as: affective, continuous and normative commitment. Affective commitment reflects a belief in the goals of an organization and a willingness to actively participate in its development; normative commitment reflects a sense of obliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…According to past authors [ 84 , 87 , 99 ]; employees may achieve excellent performance when they are committed to their organization. Additionally, [ 148 ] found that employees can give discretionary effort as well as have a greater impact on the performance and effectiveness of organizational strategies if they have been motivated as skilled and knowledgeable people to achieve their tasks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to past authors [ 84 , 87 , 99 ]; employees may achieve excellent performance when they are committed to their organization. Additionally, [ 148 ] found that employees can give discretionary effort as well as have a greater impact on the performance and effectiveness of organizational strategies if they have been motivated as skilled and knowledgeable people to achieve their tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers found that career growth components, such as professional development opportunity, promotion speed and remuneration growth, have been positively associated with employees’ commitment [ 44 , 82 – 86 ], as the committed employees are more likely to participate in the organizational improvement [ 87 , 88 ]. Organizations must offer opportunities for career advancement [ 89 ] as professional development strategies contribute to career growth which in turn can contribute to employee commitment [ 10 , 46 ], particularly to continuance commitment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this study empirically examines the role of managerial support in the relationship between employees’ prosocial motivation and organizational commitment. Bearing the former claims in mind, organizational commitment is a highly researched job attitude in the field of organizational behavior, management [ 19 , 23 ], human resources management [ 24 ], and organizational psychology [ 25 ]. This issue has attracted extensive attention from scholars and practitioners due to its positive organizational and individual outcomes such as higher productivity, job performance [ 26 ], better work-life balance, workplace stability, employee satisfaction [ 27 , 28 ], organizational citizenship behavior, better attendance, employee retention, and lower turnover intention [ 29 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…A research in Australia also confirmed the fact that the role of human resource professionals, as well as their professionalism and expertise, has grown significantly in those organizations that sought to be agile and effectively adaptable to the health crisis, and which showed a high level of trust and additional care for its employees (Aitken-Fox et al, 2020). All these activities foster organizational commitment of employees and have significant impact on the overall organizational functioning and performance (Đorđević, Ivanović-Đukić, Lepojević, & Milanović, 2020).…”
Section: The Role and Significance Of The Hr Department In A Crisis S...mentioning
confidence: 99%